Catalytic performance of a metal-free graphene oxide-Al2O3 composite assembled by 3D printing. Issue 2 (February 2021) - Azuaje, Jhonny; Rama, Adrián; Mallo-Abreu, Ana; Boado, Mónica G.; Majellaro, María; Tubío, Carmen R.; Prieto, Rubén; García-Mera, Xerardo; Guitián, Francisco; Sotelo, Eddy; Gil, Alvaro
Graphical abstract: Abstract: This paper describes the first example of a 3D printed metal-free graphene oxide-Al2 O3 (GO-Al2 O3 ) catalytic system and evaluates its catalytic performance in model transformations. A new functional architecture creates synergies to combine the excellent catalytic effect and reaction scope of graphene oxide, the chemical stability and recyclability of the ceramic support, and the versatility and control over size of 3D printing technology. The graphene oxide-Al2 O3 based catalyst presented here constitutes a step forward in the development of highly active, heterogeneous, and reusable ceramic catalysts.